Rancang Aplikasi Booking Layanan Penduduk pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bombana - Sarman; Adawiyah, Rabiah; Rasyid, Rasmiati; Muhallim, Muhlis (JISTech : Journal of Information Systems and Technology, 2024)
This study aims to design and implement a web-based service booking information system for the Department of Population and Civil Registration (Disdukcapil) in Bombana Regency. The system was developed as a solution to address various issues in administrative services, such as long queues, limited human resources, and the inconvenience faced by the public when accessing services directly. By leveraging information technology, this system allows citizens to register and book services online, thereby reducing wait times and improving the operational efficiency of Disdukcapil. The research methodology used in this study is the Waterfall model, which includes stages of requirements analysis, system design, coding, testing, and implementation. The information system was developed using the PHP programming language and a MySQL database, with an interface designed to be user-friendly. System testing was conducted through Blackbox Testing and User Acceptance Testing (UAT), which showed that all the main functions of the system worked as expected, and the majority of users were satisfied with the ease of use and efficiency provided. The results of the study indicate that the web-based service booking information system effectively enhances the quality of services at Disdukcapil Bombana Regency by reducing queue times, facilitating service access, and optimizing data management. The system also demonstrates innovation by providing a more comprehensive solution for various types of civil registration services. However, challenges such as educating the public on the use of digital technology still need to be addressed. Further development recommendations include enhancing features, integrating with other systems, and developing a mobile application to expand service reach